DETERMINATION OF SELECTION CRITERIA FOR TOMATO (SOLANUM LYCOPERSICUM L.) YIELD COMPONENT IN THE LOWLAND BASED ON PATH ANALYSIS - Marlina Mustafa; Muhamad Syukur; Surjono Hadi Sutjahjo; S. Sobir (Universitas Sembilanbelas November Kolaka, 2018)
The shifting of tomatoes cultivation from upland to lowland led to a significant decrease of tomatoes production, particularly on tomatoes varieties which are not able to adapt to lowland. Genotypes selection based on appropriate selection criteria is the most effective method to obtain tomatoes genotypes with high production in the lowland. The aim of this study was to determine appropriate selection criteria in the lowland based on high heritability value, high phenotype and genotype correlation to production component, and character relationship closeness with production component through path analysis. This study used a randomized block design with three replications. Selection criteria was chosen based on high heritability value, significant correlations in phenotype and genotype and its high direct impact on fruit weight per plant which were the number of fruits per plant and weight per fruit characters